RIFM fragrance ingredient safety assessment, 1, 3, 3-trimethyl-2-norbornanyl acetate, CAS registry number 13851-11-1. (November 2016) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Highlights: 1, 3, 3-Trimethyl-2-norbornanyl acetate safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. All endpoints were cleared using data on the target material, read across and/or TTC.